Hollow nanospheres of mesoporous Co9S8 as a high-capacity and long-life anode for advanced lithium ion batteries. (March 2015) - Zhou, Yanli; Yan, Dong; Xu, Huayun; Feng, Jinkui; Jiang, Xiaolei; Yue, Jie; Yang, Jian; Qian, Yitai
Abstract: Hollow nanospheres of mesoporous Co9 S8 are successfully synthesized by a facile solvothermal reaction followed with a high-temperature annealing in Ar/H2 . These hollow nanoparticles exhibit a reversible capacity of ~1414 mA h g −1 after 100 cycles at 100 mA g −1 . In the course of this cycling, there is a significant capacity recovery, which is associated with enhanced capacitance caused by repeated electro-chemical milling. The growth of a carbon shell on the hollow nanospheres further improves the reversible capacities at high rates, ~896 mA h g −1 after 800 cycles at 2 A g −1 . The excellent lithium-storage performances shed light on the promising potential of sulfides as a high capacity, high rate and long life anodes. Graphical abstract: Highlights: Hollow nanospheres of mesoporous Co9 S8 are synthesized by a simple process. These nanospheres show a capacity of ~1400 mA h g −1 after 100 cycles at 100 mA g −1 . There is a significant capacity recovery upon this cycling. This capacity recovery is associated with enhanced capacitive contribution. Carbon coating on Co9 S8 further stabilizes the capacity at high rates.